Spatial and temporal distribution characteristics of carbon emissions and their drivers in shrinking cities in China: Empirical evidence based on the NPP/VIIRS nighttime lighting index. (15th November 2022) - Yang, Shengdong; Yang, Xu; Gao, Xin; Zhang, Jingxiao
Abstract: Shrinking cities are a category of cities characterized by population loss, and the environmental problems of these cities are often neglected. Using panel data from 2012 to 2019, this paper investigates the spatial and temporal distribution characteristics of carbon emissions in shrinking cities in China and the driving factors. The results find that: (1) From 2012 to 2019, carbon emissions tend to increase in shrinking cities and decrease in non-shrinking cities. Due to earlier industrial development and ecological neglect, shrinking cities in Northeast China have higher carbon emissions than other regions. (2) Population size, industrial structure and public services promote the growth of carbon emissions in shrinking cities. The influence of living environment on carbon emissions in shrinking cities is not significant. There is an environmental Kuznets curve (EKC) relationship between economic level and carbon emission. (3) In shrinking cities, the increase in commuting time and distance due to spatial expansion promotes the growth of carbon emissions. Foreign investment decreases with the loss of population, which reduces carbon emissions. Technological progress gradually declines as investment in science and technology decreases, which makes carbon emissions grow. This paper clarifies the driving factors of carbon emissions in shrinking cities in China, and therefore, the findings of this paper have important reference value for the formulation of carbon reduction policies in shrinking cities in developing countries. Highlights: Carbon emissions in shrinking cities tend to grow. Shrinking cities have higher carbon emissions compared to non-shrinking cities. The characteristic factors of shrinking cities affect carbon emissions. Carbon emissions from shrinking cities have spatial effects.